Situation of the Singaporean LGBT Community - Burski, Jakub; Czapla, Karolina (International Studies. Interdisciplinary Political and Cultural Journal, 2023)
The aim of this article is to present the perception of the homosexual minority in Singapore, to summarize its history dating back to the presence of the British Empire in the Southeast Asia and to describe the current situation regarding the rights of the LGBT community. Legal changes related to the acceptance of people belonging to sexual minorities will be shown.The work consists of section on the past of the city-state and its legal code and describes the attempts by activists to influence the Singaporean government until November 2022, when sexual relations between men were decriminalized.The work demonstrates that the homosexual minority still faces problems in the legal aspect, however, thanks to the activists and the increase in social awareness, it is gradually increasing the level of acceptance of homosexuality in Singapore.